Utilization of Jarosite waste for the development of sustainable concrete by reducing the cement content. (1st November 2020) - Ray, Sonalisa; Daudi, Lubwama; Yadav, Himanshu; Ransinchung, G.D.
Abstract: In this work, the effects of using Jarosite as a partial replacement for cement were investigated. Jarosite is a waste material produced by the zinc manufacturing industry that has been utilized in concrete as a partial replacement for cement. Experimental studies have been carried out to understand the performance of Jarosite in concrete in terms of the microstructure, heat of hydration, thermogravimetric properties, and mechanical and durability properties. Laboratory investigations have confirmed that an increase in the percentage of Jarosite up to 15% resulted in an improvement in the mechanical properties of both ordinary Portland cement and pozzolanic Portland cement-based concretes. A relatively denser microstructure was observed and attributed to the fine grain structure of the Jarosite and the formation of secondary hydration products. Results of the heat of hydration and thermogravimetric analysis confirmed the occurrence of a secondary hydration reaction in the presence of Jarosite. Further, the durability characteristics of the Jarosite mixture demonstrated better performance relative to the control concrete mix. The leaching characteristics of the heavy metals in Jarosite-based concrete mixtures were predicted to be within permissible limits. Highlights: Jarosite was used as a partial replacement for cement in concrete. Optimum mechanical properties were observed with 15% Jarosite usage. A denser microstructure was observed in Jarosite based concrete. The leaching of the heavy metals are within the permissible limits.